Pengaruh Literasi Digital Menggunakan Model Pembelajaran Problem-Based Learning Terhadap Motivasi Semangat Belajar Siswa Pada Pembelajaran Informatika - Risaldi Andika Rajah; Rissal Efendi (Peneliti.net, 2023)
The purpose of this study was to find out how big the percentage of influence from Digital Literacy using the Problem-Based Learning learning model on the motivation of students' Learning Enthusiasm in Informatics learning at Christian High School 1 Salatiga. This research is a research with quantitative methods that involve measuring the level of a particular characteristic. This study uses an analysis technique or simple linear regression test to be able to determine the effect of the Digital Literacy variable using the Problem-Based Learning (X) learning model on the variable Student Learning Motivation (Y). The population in this study was taken from class X students who were at Christian High School 1 Salatiga. Sampling was used to select samples from the research population, namely students in class X-6, which consisted of 35 students. Data collection techniques were carried out using a questionnaire method with a Likert scale. The validity of the data obtained was tested using validity and reliability tests. In the test phase, the analysis requirements were tested using the Normality test, Linearity test, and Heteroscedasticity test using the Statistical Product and Service Solution (SPSS) software. The results of this study indicate that there is a positive and significant influence between Digital Literacy using the Problem-Based Learning Model on Learning Motivation at Christian 1 High School Salatiga with a value of 59.5%, while 31.5% is the influence of other variables not examined in this study.